LEGAL BASIS OF INSTITUTE OF CANCELLATION OF CONTRACT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article explores the legal grounds for contract termination in civil law. It examines theoretical concepts underlying termination, such as material breach, changed circumstances (rebus sic stantibus), and the principle of good faith. The legislation of the Republic of Uzbekistan is analyzed alongside comparative legal practices from Germany, France, the UK, and international instruments (CISG, UNIDROIT Principles). The study concludes that a flexible and equitable approach to terminating contractual obligations is essential.